Mathematical Modelling of Wildland Fires Initiation and Spread Using a Coupled Atmosphere-Forest Fire Setting; Chemical Engineering Transactions; Vol. 70 - Perminov V. A. Valery Afanasievich (2018, 2018)
Title screen